2008
DOI: 10.1158/0008-5472.can-08-1545
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Antagonize Estrogens by Glucocorticoid Receptor–Mediated Activation of Estrogen Sulfotransferase

Abstract: Glucocorticoids and estrogens are two classes of steroid hormones that have essential but distinct physiologic functions. Estrogens also represent a risk factor for breast cancer. It has been suggested that glucocorticoids can attenuate estrogen responses, but the mechanism by which glucocorticoids inhibit estrogenic activity is unknown. In this study, we show that activation of glucocorticoid receptor (GR) by dexamethasone (DEX) induced the expression and activity of estrogen sulfotransferase (SULT1E1 or EST)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 54 publications
8
122
0
1
Order By: Relevance
“…Considering that estrogens and glucocorticoids often oppose each other to regulate cellular responses (44), the observed methylation of NR3C1 may reflect an analogous role of protein arginine methylation in glucocorticoid signaling as previously described for estrogen signaling (43). Additionally, we identified Insulin Receptor Substrates 2 & 4 (IRS2 and IRS4) to be modified by MMA, suggesting that arginine methylation may be involved in insulin signaling and glucose metabolism.…”
Section: Identification Of Endogenous Arginine Mono-methylation (Mma)supporting
confidence: 63%
“…Considering that estrogens and glucocorticoids often oppose each other to regulate cellular responses (44), the observed methylation of NR3C1 may reflect an analogous role of protein arginine methylation in glucocorticoid signaling as previously described for estrogen signaling (43). Additionally, we identified Insulin Receptor Substrates 2 & 4 (IRS2 and IRS4) to be modified by MMA, suggesting that arginine methylation may be involved in insulin signaling and glucose metabolism.…”
Section: Identification Of Endogenous Arginine Mono-methylation (Mma)supporting
confidence: 63%
“…[17][18][19] Therefore, it is important to examine the expression of GR and other steroid receptors in thymic tumors.…”
mentioning
confidence: 99%
“…In the current study, we tried to determine the free E2 plasma concentration using the same ELISA kit, but the concentration was too low to be detectable, indicating the plasma E2 concentration is much lower, which is in agreement with the previous results. Additionally, because stronger uterine estrogen responses are indicative of higher levels of active estrogens and vice versa [17,46] , uterine estrogen responses are usually used to indirectly evaluate the overall level of active estrogens in the body. In this study, TM208 significantly inhibited the uterine responses because the uterine volume and weight obviously decreased after treatment with TM208 ( Figure 6B), indicating that TM208 reduced the levels of circulating estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al reported that the activation of EST is mediated by both the glucocorticoid receptor (GR) and orphan nuclear receptor liver X receptor (LXR), leading to estrogen deprivation and the inhibition of breast tumor growth in vivo [17,46] . Furthermore, these responses were not observed in EST knockout mice after treatment with LXR agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation